Dusp16 Deficiency Causes Congenital Obstructive Hydrocephalus and Brain Overgrowth by Expansion of the Neural Progenitor Pool - Zega, Ksenija; Jovanovic, Vukasin M.; Vitic, Zagorka; Niedzielska, Magdalena; Knaapi, Laura; Jukic, Marin M.; Partanen, Juha; Friedel, Roland H.; Lang, Roland; Brodski, Claude (Frontiers in Molecular Neuroscience, 2017)
Hydrocephalus can occur in children alone or in combination with other neurodevelopmental disorders that are often associated with brain overgrowth. Despite the severity of these disorders, the molecular and cellular mechanisms underlying these pathologies and their comorbidity are poorly understood. Here, we studied the consequences of genetically inactivating in mice dual-specificity phosphatase 16 (Dusp16), which is known to negatively regulate mitogen-activated protein kinases (MAPKs) and which has never previously been implicated in brain development and disorders. Mouse mutants lacking a functional Dusp16 gene (Dusp16-/-) developed fully-penetrant congenital obstructive hydrocephalus together with brain overgrowth. The midbrain aqueduct in Dusp16-/- mutants was obstructed during mid-gestation by an expansion of neural progenitors, and during later gestational stages by neurons resulting in a blockage of cerebrospinal fluid outflow. In contrast, the roof plate and ependymal cells developed normally. We identified a delayed cell cycle exit of neural progenitors in Dusp16-/- mutants as a cause of progenitor overproliferation during mid-gestation. At later gestational stages, this expanded neural progenitor pool generated an increased number of neurons associated with enlarged brain volume. Taken together, we found that Dusp16 plays a critical role in neurogenesis by balancing neural progenitor cell proliferation and neural differentiation. Moreover our results suggest that a lack of functional Dusp16 could play a central role in the molecular mechanisms linking brain overgrowth and hydrocephalus.